149k views
5 votes
Find the product.
(3x + y) (3x - 3y)

2 Answers

3 votes

Answer:

9xsq - 6xy -3ysq

Explanation:

3x x 3x = 9xsq

3x x -3y= -9xy

y x 3x = 3xy

y x -3y= -3ysq

9xsq -9xy +3xy -3ysq

9xsq -6xy - 3ysq

sq = squared

User Summit
by
5.2k points
1 vote

Answer:


9x^(2) -6xy-3y^(2)

Explanation:


(3x+y)(3x+-3y)


(3x)(3x)+(3x)(-3y)+(y)(3x)+(y)(-3y)


9x^(2) -9xy+3xy-3y^(2)


9x^(2) -6xy-3y^(2)

User Kanchirk
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.